Optimization of active variable stiffness system for controlling structural response of a building under earthquake excitation - Hejazi, Farzad; Noorzaei, Jamaloddin; Jaafar, Mohd Saleh; Thanoon, Waleed A.; Abang Ali, Abang Abdullah (Journal of Structural Engineering, 2025)
The application of modern control techniques to mitigate the harmful effects of seismic loads on building structures offers an appealing alternative to traditional earthquake resistant design approaches. In this study an attempt has been made to optimize the effect of an active variable stiffness system of a multistory building in order to reduce the displacement response of a structure, subjected to earthquake excitation using the latest most powerful computational techniques. To achieve this objective a computation procedure which is based on optimization through genetic algorithm and artificial neural network, has been developed. The computation algorithm was applied to 3 and 5 storey building structures and the response has been compared with a buildings response without any control system (uncontrolled). It was found that the developed algorithm is very effective and efficient in reducing structural responses in terms of induced displacements and prevents these responses from exceeding beyond the limit values even during strong earthquakes.